Viral suppression and self-reported ART adherence after 3 years of universal testing and treatment in the HPTN 071 (PopART) community-randomised trial in Zambia and South Africa: a cross-sectional analysis. Issue 11 (November 2022) - Macleod, David; Shanaube, Kwame; Skalland, Timothy; Limbada, Mohammed; Mandla, Nomtha; Bwalya, Justin; Schaap, Ab; Yang, Blia; Donnell, Deborah; Piwowar-Manning, Estelle; Eshleman, Susan H; Hoddinott, Graeme; et al.
Summary: Background: In 2014, UNAIDS set the target that 90% of individuals on antiretroviral therapy (ART) be virally suppressed. Here, we use data from the HPTN 071 (PopART) trial to report whether the introduction of universal testing and treatment has affected viral suppression or treatment adherence among individuals who self-reported they were taking ART, and identify risk factors for these outcomes. Methods: This was a cross-sectional study nested within the randomly selected population cohort of the PopART trial. The trial took place in 21 communities in Zambia and South Africa. Analyses included 3570 HIV-positive participants who were seen at the second follow-up visit in 2016–17 and who self-reported that they were currently taking ART. Viral suppression was defined as HIV RNA of less than 400 copies per mL from a blood sample collected during the cohort visit, and ART adherence was measured using self-reporting (reported as no missed pills in last 7 days). Prevalences of these outcomes were compared across three trial arms using a two-stage approach suitable for clustered data. Each arm consisted of seven communities, with one arm receiving a combination HIV prevention package including immediate ART initiation, one receiving a combination HIV prevention package excluding immediate ART initiation and one arm receving standard of care. Risk factors for each of the outcomes were assessed using logistic regression. Findings: Among the 3570 participants who self-reported that they were currently on ART, 416 (11·7%) of 3554 were not virally suppressed (16 were missing viral suppression status) and 345 (9·7%) of 3566 reported being non-adherent to ART (four were missing adherence status). The proportion not virally suppressed was higher in communities in South Africa (195 [16·4%] of 1191) than in Zambia (221 [9·4%] of 2363). There was no evidence that the prevalence of the outcomes differed between trial arms. There was evidence that men, younger individuals, individuals who reported participating in harmful alcohol use, and those who reported internalised stigma were more likely to be non-adherent, and not virally suppressed. Interpretation: The results assuaged concerns that early ART initiation in a universal testing and treatment setting could lead to reduced adherence and viral suppression. Funding: US National Institute of Allergy and Infectious Diseases (which is a part of the National Institutes of Health), the International Initiative for Impact Evaluation with support from the Bill & Melinda Gates Foundation, US President's Emergency Plan for AIDS Relief, and Medical Research Council UK.